2014
DOI: 10.1152/ajpgi.00272.2013
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid-borne hepatocyte growth factor protects rat pups against experimental necrotizing enterocolitis

Abstract: fluid-borne hepatocyte growth factor protects rat pups against experimental necrotizing enterocolitis. Am J Physiol Gastrointest Liver Physiol 306: G361-G369, 2014. First published January 9, 2014; doi:10.1152/ajpgi.00272.2013.-Fetal swallowing of amniotic fluid, which contains numerous cytokines and growth factors, plays a key role in gut mucosal development. Preterm birth interrupts this exposure to amniotic fluid-borne growth factors, possibly contributing to the increased risk of necrotizing enterocolitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 40 publications
(46 reference statements)
1
35
0
Order By: Relevance
“…In additional experiments, both in vitro and in vivo amniotic fluid modulated the ability of lipopolysaccharide to trigger TLR4-dependent inflammatory signalling, and these effects were mediated via EGF/EGFR [95]. It has also been suggested that these protective effects of amniotic fluid are mediated via hepatocyte growth factor [96]. …”
Section: Preventionmentioning
confidence: 99%
“…In additional experiments, both in vitro and in vivo amniotic fluid modulated the ability of lipopolysaccharide to trigger TLR4-dependent inflammatory signalling, and these effects were mediated via EGF/EGFR [95]. It has also been suggested that these protective effects of amniotic fluid are mediated via hepatocyte growth factor [96]. …”
Section: Preventionmentioning
confidence: 99%
“…In these efforts, several cytokines have been tested: EGF, heparin-binding epidermal growth factor (HB-EGF), erythropoietin, G-CSF, glucagon-like peptide (GLP-2), TGF-β 2 , and HGF. 7,42,4447 The evidence supporting the use of each agent is summarized later.…”
Section: Can Enterally Administered Cytokines Prevent Nec?mentioning
confidence: 99%
“…Jain et al 44,53,73 have examined whether enteral administration of mother’s own AF to the neonate could protect against NEC. We showed that supplementation of formula feedings with AF prevented NEC-like injury in rat pups.…”
Section: Can Enterally Administered Cytokines Prevent Nec?mentioning
confidence: 99%
“…In experimental models, the molecule C34, a 2-acetamidopyranoside (MW389) (44) and amniotic fluid (45) have reduced the incidence of experimental NEC. Epithelial growth factor (EGF) (46) and hepatocyte growth factors (HGF) (47) were found to be the mediators of amniotic fluid-derived protection. An improved understanding of the factors influencing the development of the microbiota or that modulate its composition may offer new strategies, tools, and opportunities for preterm interventions that reduce the risk of specific diseases as NEC.…”
Section: Reviewmentioning
confidence: 99%